2022
DOI: 10.3389/fphys.2022.825202
|View full text |Cite
|
Sign up to set email alerts
|

Transcription and Post-translational Regulation of Autophagy in Insects

Abstract: Autophagy attracts great attention, and numerous progresses have been obtained in the last two decades. Autophagy is implicated in mammalian neurodegenerative diseases, tumorigenesis, as well as development in insects. The regulatory mechanism of autophagy is well documented in yeast and mammals, whereas it is not fully illustrated in insects. Drosophila melanogaster and Bombyx mori are the two well-studied insects for autophagy, and several insect-mammalian evolutionarily conserved or insect-specific mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…Likewise, the negative correlation of F3, composed of hymenoptaecin , an antimicrobial peptide gene (Casteels et al, 1993), and Cyp6a14.1 , a putative detoxification enzyme gene (Mao et al, 2009), with DWV suggests a complex response to the viral pathogen, and, potentially, virally mediated suppression of important host functions. It is, however, notable that none of the genes examined in the present study are known to be associated with cellular autophagy (Li et al, 2022), which is the immune pathway shown to be affected by exposure to Sylgard‐309 (Aronstein & Saldivar, 2005; Nakamoto et al, 2012). In the future, the effects of TSS adjuvants on this pathway in adults should be further examined to better explain the treatment‐dependent increases in DWV abundance reported in our study.…”
Section: Discussionmentioning
confidence: 67%
“…Likewise, the negative correlation of F3, composed of hymenoptaecin , an antimicrobial peptide gene (Casteels et al, 1993), and Cyp6a14.1 , a putative detoxification enzyme gene (Mao et al, 2009), with DWV suggests a complex response to the viral pathogen, and, potentially, virally mediated suppression of important host functions. It is, however, notable that none of the genes examined in the present study are known to be associated with cellular autophagy (Li et al, 2022), which is the immune pathway shown to be affected by exposure to Sylgard‐309 (Aronstein & Saldivar, 2005; Nakamoto et al, 2012). In the future, the effects of TSS adjuvants on this pathway in adults should be further examined to better explain the treatment‐dependent increases in DWV abundance reported in our study.…”
Section: Discussionmentioning
confidence: 67%
“…This complex responds effectively to reduced insulin signaling, extending lifespan, and highlighting the significance of autophagy in insect longevity. Notably, the phosphorylation of Atg1 by AMPK, especially at Ser269 and Ser270, is essential for autophagy initiation in both species (Li et al, 2022;Zhao et al, 2023). Phosphorylation/dephosphorylation pathways in eukaryotes.…”
Section: Phosphorylation and Dephosphorylationmentioning
confidence: 99%
“…From a regulatory perspective, in D. melanogaster, autophagy induction is under the control of the target of rapamycin (TOR) pathway [24,[38][39][40][41]. TOR inhibition in response to stress or exposure to rapamycin causes a cellular increase in autophagic flux, i.e.…”
Section: Introductionmentioning
confidence: 99%